2017
DOI: 10.1111/ijd.13863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin cancer in Native American kidney transplant recipients

Abstract: NAKTRs have a decreased prevalence of skin cancer compared to their white counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Racial differences in malignancy risk after KTx has been identified for Black and Hispanic recipients but has not been reported for the Indigenous patients post-transplant outside of skin [22]. The risk for malignancy in our cohort was significantly lower among the Indigenous patients and there were no cases of skin malignancy in that cohort which is consistent with known decreased prevalence of skin cancer in Indigenous KTx recipients compared to Whites after transplant [23]. The increase in malignancy risk after KTx has been partly attributed to baseline risk and in our study the White cohort had significantly higher rates of malignancy prior to KTx and after KTx consistent with current literature [22].…”
Section: Plos Onesupporting
confidence: 83%
“…Racial differences in malignancy risk after KTx has been identified for Black and Hispanic recipients but has not been reported for the Indigenous patients post-transplant outside of skin [22]. The risk for malignancy in our cohort was significantly lower among the Indigenous patients and there were no cases of skin malignancy in that cohort which is consistent with known decreased prevalence of skin cancer in Indigenous KTx recipients compared to Whites after transplant [23]. The increase in malignancy risk after KTx has been partly attributed to baseline risk and in our study the White cohort had significantly higher rates of malignancy prior to KTx and after KTx consistent with current literature [22].…”
Section: Plos Onesupporting
confidence: 83%
“…Notably, over the past five years, some follow-up studies have found lower BCC:SCC ratios. 20,24,25 These results can be partially explained by the reduced trend of SCC incidence over the past 20 years in solid organ transplant recipients. 26,27 This decline is likely caused by less aggressive and more individualized immunosuppression therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There were two patients with squamous cell carcinoma (both Brigham and Women's Hospital T2a; one American Joint Committee on Cancer 8 th edition T2 and one T3) on immunosuppression due to kidney transplant and neither patient had a prior history of skin cancer or experienced recurrence. A study evaluating the prevalence of skin cancer in Native Americans kidney transplant recipients concluded that rates of skin cancer in Native Americans solid organ transplant patients seem to be much lower compared to White recipients [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is scarce literature on skin cancers in Native Americans, who represent approximately 1.3% of the total population [6]. Previous studies have estimated non-melanoma skin cancer incidence of 2% in Native Americans [7] compared to 20-30% in Whites in the U.S. [3]. Data regarding non-melanoma skin cancer characteristics, treatment outcome, and mortality in Native Americans populations is lacking.…”
Section: Introductionmentioning
confidence: 99%